Jenis - Jenis Kapang Udara Ruang Baca Di UPT Perpustakaan Universitas Tanjungpura Pontianak - Masnur Turnip, Intani Islamiati, Rahmawati, (Jurnal Protobiont, 2017)
Kapang is one of microbes found in the air and can cause several diseases. This research aims to find out the kinds of air kapang that contaminated the reading corner in the library unit of Universitas Tanjungpura Pontianak. This research was conducted from February to April 2017. The sampling method was non-volumetric air sampling and was identified by profile matching method. The result were analysed descriptively by providing pictures, table, and description. The result shows that there were 12 air kapang that are Aspergillus (In1), Aspergillus (In2), Aspergillus (In3), Aspergillus (In4), Aspergillus (In5), Aspergillus (In6), Cladosporium (In7), Curvularia (In8), Fusarium (In9), Fusarium (In10), Penicillium (In11) and Penicillium (In12). The Environment factors which influenced the existense of air kapang in the library unit of Universitas Tanjungpura Pontianak were temperature of 26-360C, humidity 32-60% and light intensity of 82-116 lux.